N-actylcysteine inhibits diethyl phthalate-induced inflammation via JNK and STAT pathway in RAW264.7 macrophages - Jin Hee Kim; Jae Hoon Lee; Yoon Jung Koo; Jong Wook Song (BMC Molecular and Cell Biology)
Abstract Background Phthalates are plasticizers that cause inflammation in several cell types and adversely affect the health of humans and animals. Nacetylcysteine (NAC) has been shown to exert antioxidant effects in various diseases. However, the effect of NAC on diethyl phthalate (DEP)-induced toxicity in macrophages has not yet been elucidated. In this study, we investigated the effect and underlying mechanisms of NAC on DEP-induced inflammation in RAW264.7 macrophages. RAW264.7 macrophages were pretreated with NAC for 2 h followed by exposure to DEP. We investigated the effect of NAC on NO, reactive oxygen species (ROS), prostaglandin E2 (PGE2), and glutathione (GSH) levels following DEP exposure. In addition, pathway-related genes including cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), mitogen-activated protein kinase (MAPK), and signal transducer and activator of transcription (STAT) were evaluated using western blot. Results Treatment with 100 and 300 µM DEHP, DBP, and DEP significantly increased the protein levels of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) compared with those in the control group. However, NAC pretreatment downregulated the levels of NO, PGE2, and ROS, elevated GSH levels, and suppressed the mRNA levels of inflammatory cytokines such as interleukin (IL)-1β, IL-6, COX-2, and iNOS compared with those in the DEP-treated group. In addition, NAC significantly reduced the levels of p-JNK and p-STAT1/3 in RAW264.7 macrophages treated with DEP. Conclusions NAC pretreatment inhibits DEP-induced inflammation via the MAPK/JNK and STAT1/3 pathways in macrophages.